Thermal Decomposition Kinetics of Fluorenone Thiosemicarbazone Complexes of Palladium(II) and Platinum(II)
Thermogravimetric (TG), derivative thermogravimetric (DTG) and differential thermal analysis (DTA) curves of PdL2 and Pt(LH